Heterosis and inbreeding depression for some quantitative and heat tolerance characters in bread wheat (Triticum aestivum L.) - Lal, Chhagan; Kumar, Vishnu; Maloo, Shiv Ratan (Journal of Cereal Research, 2013)
The present investigations were undertaken to estimate the heterosis, heterobeltiosis and inbreeding depression forsome quantitative and heat tolerance characters in three crosses involving four parents of bread wheat. Generalmeans for 1000-grain weight and grain yield were revealed as 38.39 and 16.14 gram per plant, respectively. Theaverage grain protein content, heat injury and chlorophyll stability index were exhibited as 12.58, 44.02 and14.32 per cent, respectively. For grain yield heterosis over mid parent ranged from -7.62 (Raj 3765/ PBW 343)to 16.84 per cent (Raj 3765/ Raj 4037), while heterobeltiosis ranged from 8.15 (Raj 3765/ Raj 4083) to 14.69 percent (Raj 3765/ Raj 4037). Inbreeding depression for grain yield was ranged from –17.31 (Raj 3765/ PBW 343)to 16.37 per cent (Raj 3765 x Raj 4037), respectively. The cross Raj 3765/ Raj 4037 was found to be promising fordays to heading, days to maturity, plant height, grain yield and chlorophyll stability index, while the cross Raj3765/ PBW 343 was heterotic for 1000-grain weight and grain protein content.